RtHSFA9s of Rhodomyrtus tomentosa Positively Regulate Thermotolerance by Transcriptionally Activating RtHSFA2s and RtHSPs - Huiguang Li; Ling Yang; Yujie Fang; Gui Wang; Tingting Liu (Life)
Heat shock transcription factors (HSFs) are crucial components in heat stress response. However, the contribution of the HSFs governing the inherent thermotolerance in Rhodomyrtus tomentosa has barely been investigated. We here compared the roles of RtHSFA9a, RtHSFA9b, and RtHSFA9c in heat stress tolerance. These three genes are the results of gene duplication events, but there exist vast variations in their amino acid sequences. They are all localized to the nucleus. Arabidopsis thaliana plants with overexpressed RtHSFA9a and RtHSFA9c outperformed the wild-type plants, while the over-accumulation of RtHSFA9b had little impact on plant thermotolerance. By transiently overexpressing RtHSFA9a, RtHSFA9b, and RtHSFA9c in R. tomentosa seedlings, the mRNA abundance of heat shock response genes, including RtHSFA2a, RtHSFA2b, RtHSP17.4, RtHSP21.8, RtHSP26.5, and RtHSP70, were upregulated. Transactivation assays confirmed that there exist regulatory divergences among these three genes, viz., RtHSFA9a has the highest transcription activity in regulating RtHSFA2a, RtHSFA2b, RtHSP21.8, and RtHSP70; RtHSFA9c can transcriptionally activate RtHSFA2b, RtHSP21.8, and RtHSP70; RtHSFA9b makes limited contributions to the accumulation of RtHSFA2b, RtHSP21.8, and RtHSP70. Our results indicate that the RtHSFA9 genes make crucial contributions to the thermal adaption of R. tomentosa by positively regulating the RtHSFA2a, RtHSFA2b, and RtHSP genes, which provides novel insights into the RtHSFA9 subfamily.